Damping flutter oscillation of suspension bridges - Tinh, Nguyen Van (Vietnam Journal of Mechanics, 1986)
The paper deals with flutter problem of suspension bridges in regard to damping. The formulated expression makes possible to obtain the dependence of critical wind velocity and other structural parameters. Numerical calculation, is given of the Tacoma Narrows Bridge and for some values of parameters.